ANALYSIS OF THE IMPACT OF THE PANDEMIC ON THE ECONOMY : (Case Study of Gross Domestic Product, Poverty, and Unemployment in Indonesia) - Fadlli, Muhammad Dzul; Gunawan, Muhammad Indra; Anggriawawn, Robby; Silvida, Fitra Ria (Noble Cendekia Indonesia, 2024)
This study examines the impact of the Covid-19 pandemic on Indonesia's economic conditions using a quantitative method, the Difference T-Test. The data is secondary from the Central Statistics Agency, focusing on GDP, unemployment, and poverty in 34 provinces in Indonesia. The study uses a different t-test, to test the hypothesis that there is a significant difference between before and after the pandemic covid-19. The result that indicating no significant difference in GDP before and after the pandemic, the unemployment rates before and after the pandemic are significantly different, and no statistically significant difference between poverty before and after the pandemic